APLIKASI PEMBELAJARAN BAHASA MANDARIN UNTUK TINGKAT SEKOLAH MENENGAH KEJURUAN BERBASIS ANDROID PADA SMK HARMONI KOTA BATAM - Fernaldy, Kelvin; Elisa, Erlin (LPPM Universitas Putera Batam, 2021)
The development of science and technology in China is so fast that many countries have made Mandarin as their second language and Mandarin has a very important role in the process of communication between countries and beneficial for business sector, education and other sectors. For students who take 3 levels of formal education must be taught Mandarin at school. Android devices have been widely recognized and used by teenagers to adults because the price of android devices is relatively cheaper compared to IOS and Playstore on Android provides a wide selection of applications. The purpose of this research is to improve the ability and makes it easier for students to learn Mandarin. The design of the application uses the Multimedia Development Life Cycle (MDLC) method have 6 step, which consist Concept, Design, Material Collecting, Assembly, Testing and Distribution. The design of an Android-based mandarin learning application is designed by using photo and audio media to help increase student interest in learning Mandarin and students also can learn Mandarin outside of school hours. The result of application testing is application has been function properly on android devices and available on the playstore to make it easier for students to install applications.